VECTORS AND TOOLS OF INCLUSIVE COMMUNITY DEVELOPMENT (Regional aspects of productive forces development of Ukraine, 2022)
Introduction. Today, territorial communities are a social center, a self-governing center in which civil society is formed. Creating comfortable living conditions in them, forming the preconditions for ensuring their sustainable development is a priority and urgent task of local governments. Under such conditions, the concept of inclusive development, which emerged at the beginning of the XXI century and is now actively used in various spheres and spheres of public life, becomes especially relevant.Goal. The purpose of the article is to substantiate the need to ensure the inclusive development of territorial communities, to determine its strategic goal, vectors and tools for their implementation.Methods. The following methods were used for scientific research: method of structural analysis, method of system analysis, method of abstract-logical generalization.Results. The strategic goal of inclusive development of territorial communities is formulated: creation of investment-attractive, gender-oriented, comfortable, ecologically clean territorial communities with developed infrastructure, productive small and medium business, effective governance and active community of people. The vectors of inclusive development of territorial communities are determined: creation of the institutional base of inclusive development of territorial communities; ensuring an inclusive approach to the implementation of municipal governance, the formation of local budgets, infrastructure development; development of small and medium enterprises on the basis of inclusiveness; ensuring an inclusive approach to the provision of educational, medical, cultural and administrative services, the development of silver, green, circular and digital economies, improving the standard and quality of life of the population, as well as the general social integration of society. The main tools of inclusive development of territorial communities are proposed: investment in human capital, job creation, structural transformation of the economy, development and implementation of progressive tax policy, organization of an effective social protection system, non-discrimination, social integration of all members of society.Conclusions. The use of territorial recommendations proposed in the article will allow to build investment-attractive, gender-oriented, comfortable, environmentally friendly territorial communities with developed infrastructure, well-functioning small and medium-sized businesses, effective governance and an active community of people.